METABOLIC RATES (SMR, RMR, AMR, AND MMR) OF Oplegnathus fasciatus ON DIFFERENT TEMPERATURE AND SALINITY SETTINGS - Vitas Atmadi Prakoso; Young Jin Chang (Indonesian Aquaculture Journal, 2018)
The metabolic rate of aquatic animals is closely related to oxygen concentration and influenced by internal and external factors. Despite its high value as marine fish species in South Korea, information on rock bream Oplegnathus fasciatus metabolism is scarcely available. This study observed the standard metabolic rate (SMR), routine metabolic rate (RMR), and active metabolic rate (AMR) of rock bream Oplegnathus fasciatus subjected to different temperature settings. Another observation was performed to find out the maximum metabolic rate (MMR) on rock bream subjected to different salinity settings. Fish (TL: 26.86 ± 0.29 cm and BW: 469.40 ± 38.21 g for SMR, RMR, and AMR measurement; TL: 26.7 ± 0.4 cm and BW: 451.0 ± 44.4 g for MMR measurement) were observed using respirometer (dimension = 30 cm × 20 cm × 20 cm; volume: 10.4 L) inside a recirculation systems. SMR, RMR, and AMR were measured at 15°C, 20°C, and 25°C. Meanwhile, MMR was measured at 15, 25, and 35 psu. The results showed that SMR, RMR, and AMR increased linearly by increasing the temperatures (SMR: 58.7 ± 3.2, 102.7 ± 4.3, and 157.1 ± 4.1 mg O2/kg/h at 15°C, 20°C, and 25°C, respectively; RMR: 66.0 ± 8.6, 112.6 ± 10.2, and 175.2 ± 21.3 mg O2/kg/h at 15°C, 20°C, and 25°C, respectively; AMR: 73.4 ± 7.4, 122.0 ± 6.3, and 196.7 ± 15.4 mg O2/kg/h at 15°C, 20°C, and 25°C, respectively), whilst MMR decreased by lowering salinity (48.5 ± 5.2, 61.1 ± 5.5, and 89.3 ± 14.7 mg O2/kg/hour at salinity of 15, 25, and 35 psu, respectively).